Strength-power tests are more effective when performed after exhaustive exercise in discrimination between top-elite and elite wrestlers - Özbay, S.; Ulupinar, S. (The Journal of Strength and Conditioning Research, 2022)
This study aimed (a) to analyze strength-power variables in top-elite and elite wrestlers, (b) to identify which variables allow for discrimination between them, and (c) to investigate whether the results changed when the tests were performed after exhaustive exercise. Twenty-six male wrestlers who won medals at the national championship in junior or under-23 categories participated in this study. Athletes who also won medals at the European or World Championship were assessed as top-elite (n = 13), and others as elite (n = 13). Subjects performed the leg and arm Wingate anaerobic test (anaerobic power and capacity), maximum one repetition bench press and squat test (maximal dynamic strength), handgrip and leg strength test (isometric strength), vertical and horizontal jump test (muscle power), and pull-up and push-up (strength endurance) tests. The results showed that top-elite wrestlers produced a higher output in both lower-body and upper-body Wingate average power (relative) than the elite wrestlers when the tests were performed after full rest. However, top-elite wrestlers presented higher results (relative) in all tests, except vertical and horizontal jump tests, when the tests were performed after exhaustive exercise. Furthermore, in a discriminant function analysis, the groups were correctly classified at 65.4% when the tests were performed after full rest, whereas the groups were correctly classified at 92.3% when the tests were performed after exhaustive exercise. This study indicated that the strength-power tests performed after exhaustive exercise may be more effective in discriminating between top-elite and elite wrestlers.